2022
DOI: 10.3390/polym14214500
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Production from Methanol–Water Solution and Pure Water Electrolysis Using Nanocomposite Perfluorinated Sulfocationic Membranes Modified by Polyaniline

Abstract: In this work, we report the preparation of Nafion membranes containing two different nanocomposite MF-4SC membranes, modified with polyaniline (PANI) by the casting method through two different polyaniline infiltration procedures. These membranes were evaluated as a polymer electrolyte membrane for water electrolysis. Operating conditions were optimized in terms of current density, stability, and methanol concentration. A study was made on the effects on the cell performance of various parameters, such as meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…The significantly decreased power consumption from 4.27 to 3.58 kW h m −3 H 2 at 80 mA cm −2 can be clearly observed due to the replacement of the OER by the UOR, and it can be concluded that urea-assisted water splitting needs considerably less electrical energy than overall water splitting to achieve the energy-saving hydrogen production. 73,74…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The significantly decreased power consumption from 4.27 to 3.58 kW h m −3 H 2 at 80 mA cm −2 can be clearly observed due to the replacement of the OER by the UOR, and it can be concluded that urea-assisted water splitting needs considerably less electrical energy than overall water splitting to achieve the energy-saving hydrogen production. 73,74…”
Section: Resultsmentioning
confidence: 99%
“…The significantly decreased power consumption from 4.27 to 3.58 kW h m À3 H 2 at 80 mA cm À2 can be clearly observed due to the replacement of the OER by the UOR, and it can be concluded that urea-assisted water splitting needs considerably less electrical energy than overall water splitting to achieve the energy-saving hydrogen production. 73,74 Therefore, to highlight the advantages of the urea-assisted electrolyzer in practical H 2 production, we have collected the cathodic H 2 from the constructed electrolyzer. The H 2 production rate of 0.23 mmol h À1 is attained at a voltage of 1.60 V for urea-assisted water splitting, which is 10-fold that of overall water splitting without the addition of urea (Fig.…”
Section: Her Performance In a Three-electrode Configurationmentioning
confidence: 99%
“…Methanol is a more concentrated form of carbon, making it easier to transport and store than water [2]. Water electrolysis is generally considered less efficient than MOR, as the latter requires less energy to generate the same amount of hydrogen [3]. Methanol electrooxidation is generally easier to implement than water electrolysis, as it requires fewer components and has a more straightforward process [4].…”
Section: Introductionmentioning
confidence: 99%